Infografis Penguatan Reputasi Kehumasan Pemerintah melalui Narasi Tunggal Sosialisasi Paket Kebijakan Ekonomi - Lisa Adhrianti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
This study examines  the role and elements of infographics for strengthening reputation of the government public relations conducted by the Special Task Force of the Government Public Relations on a single narrative related to the socialization of economic policy packages. This study uses case study method based on the perspective of the theory of reputation. The result shows that info graphics are able to make government’s message can be communicated attractively and support a reputation. It concludes (1) info graphics successfully synergize delivery of 13 single narratives about economic policy package through some form of design published in social media; (2) elements of info graphics are strengthened by the used of hashtag and logo “Indonesia Good” in the design of the content of policy packages supported by the four sides of reputation (credibility, trustworthiness, reliability, and responsibility), through the realization of a number of components to build a reputation namely core values, values, identity, projection and image. This article contributes to enrich the application model of reputation theory that generally applied to Corporate Public Relations rather than Government Rublic Relations communication.